Antimicrobial and cytotoxic properties of selected medicinal plants from Kavrepalanchowk, Nepal - Gyawali, R.; Adhikari, S.; Gautam, S.; Guragain, P.; Pokharel, S.; Pradhan, N.; Sijapati, S.; Shrestha, T. M. (Banko Janakari, 2015)
Antibacterial properties of Nepalese plant species - Myrica esculenta, Mahonia nepaulensis, Madhuca longifolia and Schima wallichii were evaluated on human pathogenic microorganisms: Salmonella typhi, Staphylococcus aureus and Escherichia coli. The plants were found to possess phytochemicals- saponins, glacosides, flavonoids, tannins and alkaloids. Methanolic extract from these plants showed antimicrobial activity against tested organisms. Similarly, Brine shrimp lethality test of extracts showed the LC50 values of 15.4 ppm, 136.4 ppm, 76.9 ppm and 76.0 ppm for M. esculenta, M. nepaulensis, M. longifolia and S. wallichii respectively, which suggests that these plants are less toxic to human consumption for drug purpose. Banko Janakari, A Journal of Forestry Information for Nepal Vol. 25, No. 1 Page : 15-19